(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
Taking Care of the Body’s Health in the Typika Byzantine Literature. The Tipikon, the founding document of a monastery, imposed equality of the monks from the point of view of the clothes and food. Manual labour was encouraged, as well as the intellectual activity, the monasteries also having libraries. The rules imposed in certain monasteries allowed a number of monks to live an anchorite life, but even these ones had to attend the vigil, Sunday Liturgy and common dinner during the week end. Afterwards they withdrew in the wilderness with the food needed for one week. Certain founders provided some facilities for the relatives who joined the monastic community. The nobles had even the right to have a servant, benefited of better food and even of wine. I shall present in this study some of the basic elements of body care in typika Byzantine literature in the 11th and 12th centuries.